The Effect of Cyberloafing, Leader Member Exchange and Innovative Work Behavior on Employee Performance - Sutoni Sutoni (Dinasti Publisher, 2023)
Literature Article Review of the Effect of Cyberloafing, Leader Member Exchange and Innovative Work Behavior on Employee Performance is a scientific article that aims to build a research hypothesis of the influence between variables that will be used in future research, within the scope of Human Resource Management. The method of writing this Literature Review article is by the library risearch method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are: 1) Cyberloafing affects Employee Performance; 2) Leader Member Exchange affects Employee Performance; and 3) Innovative Work Behavior affects Employee Performance.